2006
DOI: 10.1080/00087114.2006.10797916
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome numbers of the 59 species of Eucalyptus L'Herit. (Myrtaceae)

Abstract: -The paper presents the results of the chromosomal counting of 59 species of genus Eucalyptus among which 55 are newly examined. All these species possess 2n = 22 including the four species for which the numbers 2n = 20, 24 and 28 have been reported. The number 2n = 24 previously raported in 9 species appears to result from a break of the chromosome first pair very often observed in the Eucalyptus in the metaphase and especially premetaphase stage. Although some contradictory cases of aneuploid have been repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 13 publications
1
13
0
Order By: Relevance
“…A large number of hardwood families and genera possess the same haploid number and have evolved at diploid level (MEHRA, 1972;KREMER et al, 2007;OHRI and KHOSHOO, 1987;AHUJA, 1990, 1991;D'EMERICO et al, 1995;ZOLDOS et al, 1999;KUMAR and RAO, 2002;WANG et al, 2005;OUDJEHIH and BENTOUATI, 2006;CHOKCHAI -CHAMNANKIT et al, 2008;RIBEIRO et al, 2011;HYNNIEWTA et al, 2011;COULLERI et al, 2012). However, a large heterogeneity of somatic chromosome numbers is exemplified by Meliaceae with 2n=16, 20, 22, 24, 26, 28, 30, 32, 36, 38, 40, 42, 44, 46, 48, 50, 52, 54, 56, 58, 72, 78, 80, 84, 92, 100, c150, c280, c360 (STYLE and VOSA, 1971;KHOSLA and STYLES, 1975).…”
Section: Inter and Intraspecific Polyploidymentioning
confidence: 99%
“…A large number of hardwood families and genera possess the same haploid number and have evolved at diploid level (MEHRA, 1972;KREMER et al, 2007;OHRI and KHOSHOO, 1987;AHUJA, 1990, 1991;D'EMERICO et al, 1995;ZOLDOS et al, 1999;KUMAR and RAO, 2002;WANG et al, 2005;OUDJEHIH and BENTOUATI, 2006;CHOKCHAI -CHAMNANKIT et al, 2008;RIBEIRO et al, 2011;HYNNIEWTA et al, 2011;COULLERI et al, 2012). However, a large heterogeneity of somatic chromosome numbers is exemplified by Meliaceae with 2n=16, 20, 22, 24, 26, 28, 30, 32, 36, 38, 40, 42, 44, 46, 48, 50, 52, 54, 56, 58, 72, 78, 80, 84, 92, 100, c150, c280, c360 (STYLE and VOSA, 1971;KHOSLA and STYLES, 1975).…”
Section: Inter and Intraspecific Polyploidymentioning
confidence: 99%
“…In that original study by Atchison (1947), species of Psidium showed chromosome counts ranging from 2n022 to 88, strongly suggesting the occurrence of polyploidy. Twenty-three Eucalyptus species were found to have 2n022, but with two apparent aneuploid exceptions (2n024), later dismissed after observing that chromosome breaks during metaphase are commonly seen in Eucalyptus (Oudjehih and Bentouati 2006).…”
Section: Cytogenetics and Genome Sizementioning
confidence: 99%
“…Eucalypts are ideal representatives of diploids speciation with a homogeneous haploid chromosome number of n011 (2n022) based on the analysis of 135 distinct species to date. In spite of its wide ecological and morphological diversity, the genus Eucalyptus can therefore be considered as a vast karyological continuum that probably adopts a process of evolution based fundamentally on chromosome alterations (Oudjehih and Bentouati 2006). While polyploidy in Eucalyptus has not yet been observed in nature, it has been artificially induced (Janaki-Ammal and Khosla 1969), and a renewed interest in this strategy to potentially develop fast growing trees has recently emerged (Lin et al 2010).…”
Section: Cytogenetics and Genome Sizementioning
confidence: 99%
“…Grains were germinated in Petri dish and then planted in small pots and allowed to grow to a proper size for chromosome counting. The Chromosome number of all lines was counted in 5 metaphase plates by minor modification of the conventional root tip squash protocol (Oudjehih and Boukaboub, 2000;Oudjehih and Bentouati 2006;Tosun, 1999).…”
Section: Cytological Investigationsmentioning
confidence: 99%